Cytokines induce urokinase-dependent adhesion of human myeloid cells. A regulatory role for plasminogen activator inhibitors. - Waltz, D A (1993)
Differentiation of monocytic precursors often results in adhesive properties thought to be important in migration. In this study, the influence of cytokines, known to induce macrophage differentiation, on the adhesiveness of the monocytic cell line U937 was examined in vitro. Despite development of a macrophage morphology, < 5% of cytokine-stimulated U937 cells were adherent at 24 h. Addition of 1-10 nM urokinase-type plasminogen activator (uPA) induced adherence in the presence of transforming growth factor type beta-1, 1,25-(OH)2 vitamin D3, granulocyte macrophage colony-stimulating factor, or tumor necrosis factor alpha. uPA-dependent adhesiveness was reversible after 24 h of stimulation with cytokines and uPA as adherence was prevented by the subsequent addition of anti-uPA antibodies. Adherence induced by diisopropylfluorophosphate-inactivated uPA was severalfold greater than that seen with active uPA. This difference was largely due to cell-surface turnover of active uPA complexed with plasminogen activator inhibitor (PAI). These data indicate that cytokines prime monocyte progenitors for uPA receptor-mediated signals leading to adherence, continued uPA receptor occupancy is required for adherence, and PAI decreases adherence by promoting clearance of uPA/PAI complexes. Thus the interaction of uPA and PAI at the cell surface, known to affect extracellular matrix proteolysis and hence myeloid cell migration, also regulates adhesion. The coordinated regulation of these two uPA functions by PAI may enhance the migratory potential of monocytic cells.